Islamisasi Ilmu Pengetahuan Dalam Perspektif Filsafat Pendidikan Islam - Muhammad Syaifullah; Azimah Az-zahra; Husna Ibrahim; Rinanti Ito Pohan (Lembaga Pengembangan Kinerja Dosen, 2023)
Islamization is to make or bring something into Islam and make it Islam Beginning and several decades. Syed M. Naquib al Attas developed that idea into the